Parents' intention for their children to receive COVID-19 vaccine: Implications for vaccination program in Macao - Choi, Un I; Pang, Yimin; Zheng, Yu; Tang, Pou Kuan; Hu, Hao; Ung, Carolina Oi Lam (Frontiers in Pediatrics, 2022)
Introduction: The decision about vaccinating children is subject to their parents’ decision. To inform strategies that support full vaccination coverage, it is important to understand the parents' vaccination attitude and tendency to act. This study aims to investigate the intention and the factors affecting parents’ decision-making about vaccinating their children. Methods: A cross-sectional, self-administered online questionnaire was completed by parents of children aged 3-12 yeas in Macao between 07 March and 17 April 2022. The survey tool was informed by the Theory of Planned Behavior (TPB) which composes of the variable “intention” and three TPB constructs (Attitude, Subjective Norm and Perceived Behavioral Control). Respondents rated their level of agreement on the construct statements using a 5-point Likert scale. Multiple linear regression analysis was used to determine if the TPB constructs were predictors of parents’ intention.. Results: A total of 1,217 parents completed the questionnaire. The majority of participants were mothers (83.2%), aged 31-40 years (62.7%), having two or more children (74.1%), had at least one dose of COVID-19 vaccine (84.4%) and considered themselves knowledgeable about the vaccine (62.1%), all of which were significantly associated with the intention to vaccinate their children (all p<0.05). Their intention varied from negative (19.1%), neutral (38.4%) to positive (42.5%). Respondents were mostly concerned about the serious side effects that the COVID-19 vaccine (mean=3.96+1.23), highly acknowledged the expectation by the school (mean=3.94+1.15) and the community (mean=3.90+1.19) of children vaccination, and rated highly the ease of making necessary arrangement (mean=3.93+1.25). In the multiple linear regression model which explained 63.5% of the variance in the intention-to-vaccinate their children, only Attitude (B=0.52, p<0.001) and Subjective Norm (B=0.39, p<0.001) were identified as strong predictors. The major reasons for not having intention were safety concerns (n=646/699, 92.4%). Participants’ most trusted local information sources were doctors (n=682), government (n=426) and healthcare professional organizations (n=416). Conclusions: Vaccinating children with COVID-19 vaccine is a complex decision-making for parents. A key to a successful COVID-19 vaccination program is effective communication about the safety profile and the usage experiences warranting the integration of reliable information sources across different healthcare sectors.